Core-shell structured gold nanorods on thread-embroidered fabric-based microfluidic device for Ex Situ detection of glucose and lactate in sweat - Zhao, Zhiqi; Li, Qiujin; Dong, Yu; Gong, Jixian; Li, Zheng; Zhang, Jianfei (Sensors and actuators. B, Chemical, 2022)
Core-shell gold nanorods (AuNRs) with Raman reporter sandwiched was prepared as the Surface-enhanced Raman scattering (SERS) tags for detecting biomarkers in human sweat. A textile-based microfluidic device integrated SERS technology and colorimetric assay as a multifunctional sweat sensor is presented in this work. Two significant metabolites in human sweat, lactate and glucose, and the local sweat loss, were monitored and rated. Mercerized cotton thread was embroidered into the hydrophobic cotton fabric as the detection sites. Viscose thread was contacted to the embroidered pattern as the microfluidic channel. Core-shell structured Au nanorods (AuNRs@Au) sandwiched Raman reporters were prepared and deposited into the embroidered sites as SERS tags for testing target biomarkers in sweat. Through the data fitting of the SERS characteristic information of the samples with known concentration, two mathematic functions were formulated to detect the concentration of glucose and lactate in sweat accurately. The limit of detection (LOD) of physiological relevant range toward glucose (0–20 mM, S/N = 3) and lactic acid (0.1–40 mM, S/N = 3) in sweat is 0.125 μM and 0.05 mM, respectively. Field evaluation was conducted on four healthy subjects at different body positions, demonstrating the accuracy of this SERS-based assay system in the textile-based sensing band. The concentration of lactate and glucose in the sweat of the four subjects is 3.50–10.34 mM and 51.86–67.19 μM. This thread/fabric microfluidic band with a SERS-based assay system enables coherent sensing and ex situ detecting human sweat with well performance and high accuracy, which matches the results of conventional testing approaches. [Display omitted] •Core-shell structured AuNRs with Raman reporters was prepared as the SERS tags for detecting biomarkers in human sweat.•A textile-based microfluidic device with high performance was integrated with both SERS technology and colorimetric assay.•The lactate and glucose in sweat of the four subjects are accurately detected of 3.50~10.34 mM and 51.86~67.19 μM.